The Influence of Ficus deltoidea in Preserving Alveolar Bone in Ovariectomized Rats - N. I. Omar; B. Baharin; S. F. Lau; N. Ibrahim; N. Mohd; A. Ahmad Fauzi; N. Muhammad; N. M. Fernandez (Veterinary Medicine International)
Ficus deltoidea has been shown to possess antioxidant properties that could prevent the development of chronic inflammatory bone diseases. In this study, the efficacy of F. deltoidea in preventing alveolar bone resorption in osteoporotic rats induced by ovariectomy (OVX) was investigated. Twenty-four female Wistar rats were divided into four groups (n = 6) consisting of sham-operated (SO), ovariectomized control (OVXN), ovariectomized treated with estrogen (OVXP), and ovariectomized treated with F. deltoidea extract (OVXF). At the beginning of the study, two nonovariectomized, healthy rats were sacrificed to serve as baseline (BL). Treatment of the rats commenced two weeks after ovariectomy—the OVXP rats that served as positive control received Premarin® (64.5 μg/kg body weight), while OVXF rats were given F. deltoidea (800 mg/kg body weight); both agents were administered orally for two months. The negative control group of rats (OVXN) and the SO group received deionized water, also administered via oral gavage. At necropsy, morphometric assessment of the interradicular bone of the first molar was carried out using a micro-CT scanner, while quantification of osteoclasts and osteoblasts was performed histologically. The results showed that no statistically significant differences among the groups p>0.05 for bone morphometric assessment. However, trabecular thickness in the OVXF group was similar to BL, while trabecular separation and alveolar bone loss height were lower than those of the OVXN group. Histologically, the OVXF group demonstrated a significantly lower number of osteoclasts and a higher number of osteoblasts compared with OVXN (p=0.008 and p=0.019, respectively; p<0.05). In conclusion, F. deltoidea has the capacity to prevent alveolar bone loss in ovariectomy-induced osteoporosis rats by potentially preserving trabecular bone microarchitecture and to decrease osteoclast and increase osteoblast cell count.